ANALISIS PENYEBAB KURANGNYA KONSENTRASI BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Al Ahfiani, Puri; Alani, Nabella (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The level of student concentration in elementary school learning can be categorized as lacking. This can be caused by various factors, both internal and external. Lack of concentration in learning significantly impacts students' absorption and understanding of the material being taught. In addition, student behavior during the learning process also greatly affects concentration in the learning process. This study aims to analyze the factors that cause students' lack of concentration in learning. This study uses a qualitative research method with a descriptive research type. The results show that students' concentration in learning is still considered lacking, this can be seen from the lack of optimal learning concentration indicators. Lack of student concentration in learning is caused by several factors, namely internal factors including interest, boredom, and negative perceptions held by each student. Meanwhile, external factors such as less than conducive environmental conditions can disrupt the concentration of other students, starting from students who talk, tease, and engage in activities outside of learning.